(3OSJhQ GddZIs - (3CHh YHO Gddg HOjY GdReGf GdMSjf Hf EHQGgje GdfWfRj GdCUHgGfj, Pj GddSGfjf,J (B499 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHOY GdYGde HbOQJg hHYO agPG OSJhQ GddZI GdeCKhQI GdeJfbOI ef GdcJH GdeYJeOI GdeTghQI s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg HGH ai GdYOO hefge ef jcSQ GdTjf ajbhd YTQI hGKfJG YTQI Zdi JSY YTQI hJKHJgG ai GdYTQI s
(3HChdg agQSs
(3HgG fXGe GdJYbjHIs
(3HgG LOGhds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B229s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B754s
Keywords: (3GddZIs